Preeclampsia and level of oxidative stress in the first trimester of pregnancy - Bogavac, Mirjana; Jakovljević, Ana; Stajić, Zoran; Nikolić, Aleksandra; Milošević-Tošić, Mirjana; Dejanović, Jadranka; Lozanov-Crvenković, Zagorka (Vojnosanitetski pregled, 2017)
Background/Aim. Preeclampsia (PE) is a multisystemic syndrome that complicates 5–8% of all pregnancies. The aim of this study was to evaluate the biochemical parameters of oxidative stress in the first trimester of pregnancy in patients with preeclampsia, with the purpose of comparing the level of oxidative stress with normal pregnancy. Methods. The study was conducted as a prospective study. It included totally 107 pregnant women divided into two groups. In the study group (n = 33) there were women who developed preeclampsia in the current pregnancy. The control group (n = 74) included healthy pregnant women. Blood samples were taken between 11th and 14th weeks of gestation, and the values of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and total antioxidant status (TAS) were determined in serum by enzymatic colorimetric methods. Results. The values of SOD and GHS-Px were statistically higher in the study group, while the values of TAS were statistically higher in the control group. The level of TAS inversely correlated with GSH-Px and SOD, but there is no statistically significant correlation between GSH-Px and SOD in the study group. Conclusion. The results of this study suggest a higher level of oxidative stress in the first trimester of pregnancy with preeclampsia, which may indicate that the initiation and development of pathophysiological processes underlying preeclampsia start much earlier than the clinical syndrome exhibit.